Funciones desempeñadas en el área de auditoría de la Oficina Zonal Chimbote de la Superintendencia Nacional de Aduanas y de Administración Tributaria - Cruz Rodriguez, Anthony Josmell (2018)
In this report, the procedures performed by an auditing verifier in an enforcement action (partial inspection, information crossing, waiver of VAT exemption, among other procedures) and how to improve the tax culture during the performed functions will be discussed This also explains some experiences obtained with the accountants of the companies in Chimbote, own of the same functions performed. All the control actions carried out as an auditing verifier were carried out in accordance with the provisions of current tax regulations, such as the Tax Code, the Income Tax Law, the I.G.V. and I.S.C., Regulation of Payment Vouchers, Regulation of the Inspection Procedure of SUNAT, etc. In the enforcement actions, from a home inspection to a final inspection, taxpayers were encouraged to have greater participation in the tax part of their companies, as well as greater communication between owner and accountant. The accountants were encouraged to communicate more of their functions to the owners, as well as providing added value to their work, to change the bad perception that owners have about the accountants since they only think that they are bookkeepers when they can provide greater benefits to the company since they are the ideal professionals for the development of the company. During all the control actions, it was promoted to improve the tax culture in the taxpayers, absolving any doubt or query. In this same line, the SUNAT is also promoting to improve the tax culture from the schools, universities and educational institutions for a better country.